Yielding behavior and traffic conflicts at cyclist crossing facilities on channelized right-turn lanes. (May 2018) - van Haperen, Wouter; Daniels, Stijn; De Ceunynck, Tim; Saunier, Nicolas; Brijs, Tom; Wets, Geert
Highlights: A behavioural and conflict observation study was conducted, examining 1366 interactions. Independent of the priority rule, cyclists cross first at CRTLs in the majority of cases. During most interactions at locations where cyclists should yield, motorists give their priority away willingly. A possible influence of the priority rule on conflict severity was found. Abstract: Channelized right-turn lanes (CRTLs) improve traffic flow efficiency, enabling right-turning drivers to bypass traffic lights at signalised intersections (for right-hand drive countries). Many CRTLs provide crossing facilities for pedestrians and cyclists. Previous studies examining the safety performance of CRTLs indicate that they increase overall safety levels but hint that safety issues regarding vulnerable road users exist. This study investigated these issues through site-based observations of yielding behavior and evaluated the effect of the priority rule on cyclists' safety in two CRTL designs. Four locations in Belgium were selected for video observations: two where the priority rule favoured cyclists and two where motorists had priority. With regard to yielding, four types of crossing behavior were identified and defined. Independent of the priority rule, cyclists crossed the conflict zone first in most interactions without taking the initiative to cross first. Underlying reasons for motorists willingly giving away their right-of-way could not be determined, but possible courtesy or fear of inflicting injuries at vulnerable road users might be at hand. A safety evaluation was performed using two traffic conflict indicators (TTCmin and the TA value). High correlations between the two indicators were found (r 2  > 0.83), but no conclusions about the safest priority rule for cyclists could be drawn. The results hinted, however, that locations with motorist priority and cyclists crossings from right to left (from the driver's point of view) yields the highest proportion of safety critical events.